Estimating workability of steam boilers superheaters considering with the high temperature creep and uniform chemical corrosion - Yefimov, Aleksander; Romashov, Yury; Kavertsev, Valerii (Національний технічний університет "Харківський політехнічний інститут", 2019)
It is proposed theoretical estimating workability of steam boilers superheaters on the base of considering the influence of a high-temperature uniform chemical corrosion on of a high-temperature creep of superheater pipes on account of stresses redistributions the pipes walls due to their thickness decreasing. The high-temperature uniform chemical corrosion is presented by the well-known time and temperature depend-ences of the height of damaged material. The high-temperature creep is considered using the well-known incremental-type theory taking into account the Cachanov-Rabotnov scalar damage parameter. It is proposed the mathematical model of state of superheaters pipes in the form of initial-boundary-value problem in the domain with the moving boundary. The differential equations, initial and boundary conditions of that problem are corresponded to the well-known in the theory of high-temperature creep. Moving of the boundary is corresponded to the well-known time dependence of the height of damaged material due to the high-temperature uniform chemical corrosion. Although, the used theory of creep and the used regularities of uniform corrosion are well-known separately, considering the influence of uniform corrosion on the creep is the complicated problem due to the moving boundary in the corresponded initial-boundary-value problem. It is shown, that the spatial variable replacement allows to reduce the proposed initial-boundary-value problem with the moving boundary to the initial-boundary-value problem with the fixed normed boundary, that allows to simplify numerical solving of the considered problem. The method of lines is discussed for solving the initial-boundary-value problem, representing the mathematical model of the state of pipes of superheaters.

Пропонується теоретична оцінка працездатності пароперегрівачів парових котлів на основі врахування впливу високотемпературної рівномірної хімічної корозії на високотемпературну повзучість труб пароперегрівача через перерозподіл напружень стінок труб через зменшення їх товщини. Запропоновано математичну модель стану труб пароперегрівачів у вигляді початково-крайової задачі з рухомою границею. Показано, що заміна просторової змінної дозволяє звести запропоновану початково-крайову задачу з рухомою границею до початково-крайової задачі з фіксованою границею, що дозволяє спростити чисельне рішення даної задачі.
Оцінка працездатності пароперегрівачів парових котлів з урахуванням високотемпературної повзучості і рівномірної хімічної коррозии
Keywords: steam boiler; life time; damage parameter; initial-boundary-value problem; moving boundary; method of lines; ресурс; рівномірна корозія; високотемпературна повзучість; параметр пошкоджуваності; початково-крайова задача; рухома границя; метод прямих